2018
DOI: 10.1080/0020739x.2018.1458340
|View full text |Cite
|
Sign up to set email alerts
|

An incentivized early remediation program in Calculus I

Abstract: Math 1190 Exam 1 Part 1 Retake Directions:• You have 25 minutes to complete this exam. The exam is worth 35 points (out of 100) of your Exam 1 grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…As expected, substantial evidence that remediation activities have an effect on the academic performance of the students in the experimental group was observed. The result of the current study is parallel to other studies that also provided positive results: Lin and Liu (2017), Radzi et al (2017), Vandenbussche et al (2018), Zygouris et al (2017), Dabkowska and Snovski (2016). However, there are also studies that contradict the ideas of the effectiveness of remediation activities.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, substantial evidence that remediation activities have an effect on the academic performance of the students in the experimental group was observed. The result of the current study is parallel to other studies that also provided positive results: Lin and Liu (2017), Radzi et al (2017), Vandenbussche et al (2018), Zygouris et al (2017), Dabkowska and Snovski (2016). However, there are also studies that contradict the ideas of the effectiveness of remediation activities.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, we also considered studies that examined remedial strategies in general instead of focusing solely on remedial exams but implemented them in different ways. Vandenbussche et al ( 2018 ) reported that a 2-hour revision program with teacher support between the initial and re-take exams was associated with higher student success, indicating that a lack of prerequisite knowledge presents a significant barrier for students. Additionally, Asio and Jimenez ( 2020 ) found significant academic improvement in fifth-grade students’ scores after implementing remediation activities in the subject of Technology and Livelihood Education (TLE).…”
Section: Discussionmentioning
confidence: 99%
“…The Early incentivized remediation program [29] addresses the issue of lack of readinessstudents entering the course with weak prerequisite knowledge. Research has shown that prerequisite weakness impedes students' learning [23]; moreover, it inhibits their ability to complete simple tasks even when they demonstrate an understanding of the underlying calculus concept.…”
Section: Early Remedial/summer Bridging Programsmentioning
confidence: 99%